Does the health information system in Jordan support equity to improve health outcomes? Assessment and recommendations - Ahmad H. Alnawafleh; Hoda Rashad (BMC, 2024)
Abstract Background This study is based on extensive evidence-based assessments. The aim of this paper is to evaluate how well Jordan's health information system (HIS) incorporates social determinants of health inequity (SDHI) and to propose suggestions for future actions. Methods An extensive evidence-based assessment was performed. A meta-synthesis of the inclusion of the SDHI in the HIS in Jordan was conducted. After searching and shortlisting, 23 papers were analyzed using Atlas.ti 9.0 employing thematic analysis technique. Results The HIS in Jordan is quite comprehensive, comprising numerous data sources, various types of information, and data from multiple producers and managers. Nevertheless, the HIS confronts several obstacles and fails to ensure the timely and secure publication of available data. The assessment of the inclusion of the SDHI in the HIS showed that the HIS allows for the measurement of progress in relation to social policies and actions but has a very limited database for supporting the inclusion of health inequity measures. One reason for the difficulty in identifying fairness is that certain crucial information necessary for this task cannot be obtained through the available institutional HIS or population survey tools. Additionally, relevant modules for fairness may be missing from population surveys, possibly due to a failure to fully utilize the capabilities of the institutional HIS. Conclusion There are opportunities to make use of Jordan's dedication to fairness and its already established strong HIS. Some social determinants of health exist in the HIS, but much more data, information, and effort are needed to integrate the SDHI into the Jordanian HIS. A proposal from a regional initiative has put forward a comprehensive set of indicators for integrating SDHI into HIS, which could aid in achieving health equity in Jordan.